The Effect of Motivation, Incentives, and Training on Employee Performance at Bumitama Gunajaya Agro in West Kalimantan - Theo Andre Dominiko; Natalia Christiani; Rismawati Sitepu (Journal Research of Social Science, Economics, and Management, 2026)
Labor productivity is a key element in the operational success of the palm oil plantation industry. Bumitama Gunajaya Agro (BGA) faces challenges in improving employee productivity, including high absenteeism, low work efficiency, and a productivity gap compared to workers from other regions. This research is driven by the company’s need to enhance work effectiveness and productivity through optimal human resource management. In this context, motivation, the provision of incentives, and training programs are considered crucial variables that can sustainably improve employee performance. Motivation, incentives, and training are key factors believed to significantly enhance employee performance and productivity. The objective of this research is to analyze the factors affecting labor productivity and to develop strategies to enhance the effectiveness of working days. This research uses a quantitative approach with descriptive and causal research designs. Data were collected through surveys using Likert-scale questionnaires and direct field observations. The collected data were tested for validity and reliability, and analyzed using multiple linear regression with the help of SPSS software. The results are expected to show that motivation, incentives, and training significantly influence employee performance, both partially and simultaneously. These findings are anticipated to contribute to policy-making and the development of human resource strategies, particularly in enhancing the productivity and work effectiveness of local employees in plantation environments. The practical implications of this study may serve as a foundation for designing fair incentive systems, targeted training programs, and motivation approaches that align with the characteristics of Bumitama Gunajaya Agro.